2005
DOI: 10.1007/s10541-005-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Thiol:Protein Disulfide Oxidoreductase from Wheat (Triticum aestivum L.) Grain

Abstract: Biochemical properties of a homogenous preparation of thiol:protein disulfide oxidoreductase (TPDO, EC 1.8.4.2) isolated for the first time from mature wheat (Triticum aestivum L.) grain were studied. According to polyacrylamide gel electrophoresis data, the molecular weight of TPDO is around 167 kD, the enzyme consisting of two subunits of 77 and 73 kD, which differentiates TPDO from known enzymes of SH/SS-metabolism of wheat caryopses. In substrate specificity and enzymatic characteristics (pH and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…d 0 Aloisio et al reported the cloning, chromosomal assignment, sequencing, and expression analysis of the complete set of genes encoding the PDI and PDI-like proteins in bread wheat (36). Among these genes, only group II (i.e., TaPDIL2-1) has been identified and purified (37). After quantifying nine wheat PDI and PDI-like gene transcripts, the presence of TaPDIL1-1, TaPDIL2-1, TaP-DIL4-1, TaPDIL5-1, TaPDIL6-1, TaPDIL7-1, and TaPDIL8-1 transcripts was detected in 38 day postanthesis caryopses, when the deposition of seed storage reserves decreased and seeds began the process of desiccation (36).…”
Section: Resultsmentioning
confidence: 99%
“…d 0 Aloisio et al reported the cloning, chromosomal assignment, sequencing, and expression analysis of the complete set of genes encoding the PDI and PDI-like proteins in bread wheat (36). Among these genes, only group II (i.e., TaPDIL2-1) has been identified and purified (37). After quantifying nine wheat PDI and PDI-like gene transcripts, the presence of TaPDIL1-1, TaPDIL2-1, TaP-DIL4-1, TaPDIL5-1, TaPDIL6-1, TaPDIL7-1, and TaPDIL8-1 transcripts was detected in 38 day postanthesis caryopses, when the deposition of seed storage reserves decreased and seeds began the process of desiccation (36).…”
Section: Resultsmentioning
confidence: 99%
“…72 The optimum temperature for TPDO activity was established at 36 °C. 70 Gluten weakening was observed in wheat growing at high temperatures (37/28 °C, day/night) 73,74 and might be connected to the activity of enzymatic systems that are similar to those of TPDO.…”
Section: Applied Liquidmentioning
confidence: 98%
“…We managed to extract and purify a GSH-dependent protein, thiol:protein-disulfide oxidoreductase (TPDO, EC 1.8.4.2), from wheat grain; this protein catalyzed the cleavage of disulfide bonds in acetic-soluble gluten proteins (Figure ) and reduced their capacity to aggregate . The enzyme was classified as a Grx-like protein because the molecular masses of the native TPDO protein (approximately 167 kDa) and its two subunits (77 and 73 kDa) significantly exceeded the molecular mass of typical glutaredoxins (12–14 kDa) and typical wheat PDI (60 kDa) . The maximum level of TPDO activity occurred between the third and fifth weeks after anthesis (WAA), in a period of maximum synthesis of storage proteins in wheat kernels.…”
Section: Regulation Of Storage Protein Polymerization By Low M R Redo...mentioning
confidence: 99%
See 1 more Smart Citation